Promotion of Natural Galangal Plants as a Substitute for Reppellent Chemicals Against Anopheles Spp Mosquitoes - Khomsatun; Santjaka, Aris; Subagiyo , Agus; Wachid Bambang Suharto, Abdul (International Proceedings of Nusantara Raya, 2023)
Mosquito control using natural repellent is one alternative to malaria vector control. Betel (Piper bettle, Linn) which contains essential oils, alkaloids, flavonoids, saponins, tannins, eugenol, and kavicol is one plant that has antibacterial power, fungicide, insecticide and antioxidant. The purpose of the study was to analyze the protective power of galangal extract concentrations of 5%, 10%, 15% and 20% against Anopheles spp mosquitoes. The research method used is an experiment in the laboratory. Anopheles sp mosquitoes are obtained from hatching eggs. Galangal extract concentrations of 5%, 10%, 15% and 40% were tested for repulsion or protection against Anopheles spp mosquitoes. Observation of the number of mosquitoes that land on guinea pigs is carried out every hour starting from the 1st hour (immediately after smearing) until the 18th hour. The effective protection of betel leaf extract is if the protective power is ≥90%. The results showed that the protective power of betel leaf extract against Anopheles spp at a concentration of 5% as much as 11%, a concentration of 10% as much as 38%, a concentration of 15% as much as 67% and a concentration of 20% as much as 90%. Effective protection power is 20% concentration with 90% protection power. This is in accordance with the Pesticide Commission (1995, p.2) which states that repellent is considered effective if its protective power ≥ 90%. The public can use galangal extract with a concentration of at least 20% as a repellent against mosquitoes, especially Anopheles spp. Other researchers can conduct similar studies using extracts from other types of plants.